IMPLICATION OF HUMORAL IMMUNITY MECHANISM IN DEVELOPMENT OF CHRONIC GENERALIZED PERIODONTITIS OF I-II SEVERITY IN PERSONS WITH PARASITIC INVASION - N. Savel'eva (Ukrainian Medical Stomatological Academy, 2016)
This article presents the clinical study researching results, the objective of which are the role and contribution of autoimmune respondent humoral components of I-II severity chronic generalized periodontitis (CGP) pathogenesis in patients with associated parasitic invasion. The research program included determining serum concentration of autoantibodies to collagen, elastin and periodontal AG, complement activity and circulating immune complexes (CIC) concentration. Statistical materials processing was made by using mathematical statistics for data analysis. The blood serum study of CGP of I and II stages patients with parasitic invasion and patients with CGP of I and II stages without parasitic invasion showed the presence of periodontal tissue autoantibodies. Tissue antibody level in patients with CGP of I and II stages with parasitic invasion was slightly higher than in patients with CGP of I and II stages without parasitic invasion, and in II stage CGP patients both with and without parasitic invasion was correspondingly higher than in patients with CGP of I stage. Patients with CGP of I and II stages with parasitic invasion, in contrast to the patients without parasitic invasion were revealed an increase in blood levels of circulating immune complexes, patients with CGP of II stage plus parasitic invasion showed complement activity increase. Autoantibodies level to collagen and elastin of the surveyed persons did not exceed normal values. The findings received suggest that in addition to autoantibodies, circulation immune complexes and activated complement system both participate in development and maintenance of inflammation in patients with CGP plus parasitic invasion over against CGP patients without parasitic invasion.